Earthworm Extract Lumbricus Rubellus and Pheretima SP Against Salmonella Typhi and Staphylococcus Aureus Bacteria: A Literature Review - Wahyuni Nasution; Ali Napiah Nasution; Sri Lestari Ramadhani Nasution (PSPP JOURNALS, 2021)
The aims of the study is to discusses Earthworm Extract Lumbricus Rubellus and Pheretima Sp Against Salmonella Typhi and Staphylococcus Aureus Bacteria. Antibacterial measurements showed that the ethylacetate fraction showed the strongest inhibition zone when compared to the ethanol extract against Salmonella typhi. The biochemistry of earthworm extract is also useful for improving the nervous system. The administration of Lumbicrus earthworms extract can increase the regeneration of damaged nerve cells. The content of the earthworm Lumbricin-I can be used as an antibacterial. Morphological and morphological observations showed changes in Staphylococcus aureus bacteria exposed to extracts of marine worms Nereis sp